Diplomasi Komersial Indonesia dalam Promosi Investasi Industri EV Tahun 2019 – 2022 - Suryodarsono, Wahyu; Sudiarto, Tatok Djoko (Intermestic: Journal of International Studies; Vol 9 No 1 (2024)DO - 10.24198/intermestic.v9n1.5, 2025)
In solving challenges related to the development of the EV industry, one of the steps taken by Indonesia is to build cooperation and practice commercial diplomacy with various parties, including multinational automotive business actors. This study aims to understand the differences in the pattern of commercial diplomacy between Indonesia and its partner countries, namely South Korea, China, and Japan, also its relation to the strategy and influence of the target object of investment promotion in the EV industry from 2019 to 2022. Data were analyzed using the verification and triangulation method based on the concept of commercial diplomacy by Potter (2004), and investment promotion strategies according to Wells and Wint (2000). The results of the study show that there are differences in the pattern of the stages of commercial diplomacy, the investment promotion approach, and characteristics of investors in the context of Indonesia for each of the countries studied.